Profile of diseases prevalent in Datia District of Madhya Pradesh, India - Mishra, Nalini; Barde, Pradip V.; Awasthi, Sarvesh; Kumawat, Archana; Gaur, Rajesh; Singh, Pushpendra; Srivastava, Suyash; Das, Aparup (Frontiers in Public Health, 2022)
Background and objectives Exploring the disease profile in a defined area helps policymakers to understand local health issues. It is essential to collect such information in countries, like India, which have a wide range of socioeconomic, geographic, and cultural diversity. Madhya Pradesh is the second largest state of India and has diversified populations living in urban, rural, and tribal areas. In this study, we performed a hospital record-based analysis to find out the status of different diseases in various outpatient departments (OPDs) of the District Hospital where patients from both rural and urban areas are treated. Materials and methods The retrospective data was collected from medical records available for the period September 2018 to September 2020. These datasets were analyzed to determine the most common presentations among patients. Results and conclusions A total of 138,756 records of patients were available for this study, whose department-wise analysis revealed that most records were related to respiratory tract infection, superficial dermatophytosis, anemia among women, suppurative otitis media, and pneumonia. This study provides a broad overview of the overall health issues of people living in rural and urban areas of Datia. However, a major limitation of the study was that other correlations with age and gender were not established due to the absence of such information. Nonetheless, these findings will help policymakers and researchers to set the agenda for interventions and set goals for achieving better health for all people including those living in rural and tribal regions.